How are professionals recruited by external agents in misconduct projects? The infiltration of organized crime in a university. (September 2019) - Radaelli, Giovanni; Guerci, Marco; Cabras, Federica; Dalla Chiesa, Nando
Private firms, crime organizations or states may successfully recruit professionals in misconduct projects. How they do so remains, however, under-investigated. Past studies mostly take professionals' perspective, or limit the organizational initiative of external agents to perverse incentives and threats. Our study shows instead how external agents may penetrate governance bodies and professional events to recruit and control professionals, who are both aware of and reluctant toward misconduct. Our longitudinal case study used judicial and non-judicial sources to analyse how a mafia clan infiltrated Troy University, and controlled the trade of exams and admissions for decades. The clan selected Troy University because of the presence of professors pre-disposed toward misconduct. The clan infiltrated the pre-disposed professors inside governance bodies and students inside academic events to recruit the reluctant professors with peer pressures, situated threats and administrative controls. It then exploited a generalized code of silence to control professionals for years. Overall, the study highlights the combination of perverse and pervasive mechanisms to recruit professionals; the role of corrupt professionals as linchpin between external agents and reluctant peers; and the perverse exploitation of normal professional practices of autonomy, trusteeship and multiple embeddedness.